Persepsi Guru terhadap Penggunaan Google Dokumen dalam Proses Mengajar dan Belajar - Efrina, Yofi (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2019)
Google Docs is a free web-based application for creating, editing, and collaborating. This systematic review shows that using multiple Google documents results in the development of learning and teaching English. Writing is the biggest language skill investigated. Google Docs is a version of Microsoft Word that offers collaborative features that can be used to facilitate teaching and learning in language classes. The method used in writing this paper is a literature study based on collecting data and information related to the teacher's perception of the use of Google Docs in the teaching and learning process. This paper shows the teacher's perception of the use of Google documents in the teaching and learning process in the classroom. There are four overarching topics that develop from the reactions given by the teacher's confession. These fundamental topics are student engagement, classroom adaptability, educator and student reinforcement, and timing skills.